Outcomes and management strategies for graft failure after umbilical cord blood transplantation. Issue 12 (26th September 2014) - Singh, Harshabad; Nikiforow, Sarah; Li, Shuli; Ballen, Karen K.; Spitzer, Thomas R.; Soiffer, Robert; Antin, Joseph H.; Cutler, Corey; Chen, Yi‐Bin
<x xml:space="preserve">Abstract</x> Graft failure is a life‐threatening complication after allogeneic hematopoietic stem cell transplantation (HSCT). Graft failure is more prevalent after umbilical cord blood transplantation (UCBT) compared with conventional adult stem cell sources. We identified 21 consecutive patients who experienced graft failure after UCBT at our center between 2004 and 2013 and describe their treatment strategies and outcomes. Two patients experienced early death. Seven patients had return of autologous hematopoiesis including 1 patient who was given previously collected autologous stem cells. Twelve patients received a second early HSCT, six from separate UCB units and six from a haploidentical donor. With a median follow‐up of 33.2 months for surviving patients, 3‐year PFS is 23% and 3‐year OS is 37%. Of the six long‐term survivors without relapse, four received a second HSCT from a haploidentical donor with post‐HSCT high‐dose cyclophosphamide based GVHD prophylaxis. This strategy appears safe and merits further investigation in this setting. Am. J. Hematol. 89:1097–1101, 2014. © 2014 Wiley Periodicals, Inc.